Analysis Anthropopedagogica of the impact on the ways of perceiving time, space, reality and real - Cárdenas Lopez, Gustavo Adolfo (Rastros Rostros, 2021)
Education has always been determined by its relationship with technology, however, only during the first twodecades of the 21st century, the impact of technology on education came to be perceived directly, that is,there was a technological change that It implied a transformation of the school as a territory, leaving aside itsphysical location, to become another territory, with different characteristics and, therefore, different ways ofexercising power but, in turn, creating new forms of to resist. Now, these new forms of power and resistanceare not alien to changes in the perception of time and space, which also leads to new reflections on the human,reality and reality.
Keywords: education; technology; space; time; human; reality; real